Avaliação da política de parques tecnológicos: desvendando os potenciais desenvolvimentos locais e globais de regiões a partir de um modelo lógico - Mello, Patricia Alencar Silva (2019)
The main contribution of this thesis is a proposal to evaluate the capacity of Science and Technology Parks (STP) to generate regional development. Although from these environments have been expected to fulfill multiple functions, there is still no empirical research on their local and global contexts in a government perspective. Aiming to fill this gap, this thesis proposes a logical model that guides the performance of STP. Through this model, we investigate the parks’ main objectives: (i) at the local level, to catalyze activities based on science, technology and innovation by gathering strategic actors and recombining regionally accumulated productive knowledge; and (ii) at the global level, to connect regions to global networks, not only by attracting leading companies worldwide and internationalizing local companies, but also by allowing the access of new actors to the global economy. Several theoretical approaches are useful for this analysis: (i) those that seek to evaluate public policies, based on logical models (Ferreira et al., 2009; McLaughlin & Jordan, 2015); (ii) the ones theorizing economic complexity combined with global production networks and the logic of forming complex networks that, although global, are contextually rooted (Coe & Yeung, 2015; Hausmann et al., 2014); and (iii) those which elucidates regional development by the local buzz and global pipelines effect and the formation of gateway cities - intermediate cities of emerging countries which are potential articulators of these networks (Aarstad et al., 2016; Bathelt et al., 2004; Scholvin et al., 2017). All of these theories aim to compose local contexts with larger analytical and spatial categories. Still, they have not yet been combined in empirical studies analyzing the role that innovation environments like STP can play as a strategic policy in this process. This thesis presents three articles that aim to fill this gap The first article proposes a logical model of STP. The second, based on this logical model and using mixed methods, investigates the economic effect of the regional policy Paulista System of Environments of Innovation (SPAI) that accredit STP in São Paulo. The third article unveils the gateway city aspect catalyzed by the Technological Park of São José dos Campos, São Paulo’s first experience supported by SPAI. In the conclusion, we emphasize the importance to monitor and evaluate Brazilian STP, a task that can be done by the logical model proposed in the thesis, which remains open to constant adaptations and improvements. STPs following this proposal could bring not only economic gains, but also positive results in academic, entrepreneurial, urban and social terms as stated in their logic 12 model.. We also emphasize the importance of establishing a baseline for gathering information from each experience and for applying different methodologies, such as those proposed in this thesis. With such proposals, we hope that new STPs will be more efficiently planned, and that the ones already operating would be improved. This way, we aim to provide inputs for alternative paths for regional development, through policies that are in line with the current globalized world.